2016
DOI: 10.3198/jpr2015.10.0064crg
|View full text |Cite
|
Sign up to set email alerts
|

Registration of AO‐1012‐29‐3‐3A Red Kidney Bean Germplasm Line with Bean Weevil, BCMV, and BCMNV Resistance

Abstract: The bean weevil (Acanthoscelides obtectus Say) is an aggressive post‐harvest pest of the common bean (Phaseolus vulgaris L.). Bean common mosaic virus (BCMV) and Bean common mosaic necrosis virus (BCMNV) are important seedborne diseases of dry bean in the Americas and Africa. The development of bean lines that combine resistance to BCMV, BCMNV, and bean weevils can help to reduce yield loss during the growing season and avoid seed damage during storage. AO‐1012‐29‐3‐3A, (Reg. No. GP‐299, PI 675563) is a multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 16 publications
0
38
0
Order By: Relevance
“…A permutation test (Doerge and Churchill, 1996) for each trait was conducted in QTL Cartographer (1000 permutations) to determine a genome-wide LOD threshold at p = 0.05 for declaring a QTL significant. AO-1012-29-3-3A is a determinate (Type I) dark red kidney bean breeding line that was developed and released cooperatively by Sokoine University of Agriculture, Oregon State University, USDA-ARS, and the University of Puerto Rico (Kusolwa et al, 2016). The amount of phenotypic variance explained by a QTL at a given test position was determined using the R 2 from the QTL cartographer software program.…”
Section: Qtl Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A permutation test (Doerge and Churchill, 1996) for each trait was conducted in QTL Cartographer (1000 permutations) to determine a genome-wide LOD threshold at p = 0.05 for declaring a QTL significant. AO-1012-29-3-3A is a determinate (Type I) dark red kidney bean breeding line that was developed and released cooperatively by Sokoine University of Agriculture, Oregon State University, USDA-ARS, and the University of Puerto Rico (Kusolwa et al, 2016). The amount of phenotypic variance explained by a QTL at a given test position was determined using the R 2 from the QTL cartographer software program.…”
Section: Qtl Analysismentioning
confidence: 99%
“…This resistance, however, was more effective against Z. subfasciatus than against A. obtectus (Osborn et al, 1988;Harmsen, 1989;Myers et al, 2001). Resistance in G40199 has been successfully transferred into common bean, resulting in the development of resistant common bean cultivars (Kusolwa et al, 2009(Kusolwa et al, , 2016. In addition to resistance found in the wild common bean, resistance is also found in wild and cultivated species of tepary bean (P. acutifolius A.…”
mentioning
confidence: 99%
“…Kusolwa et al (2016) also registered the red kidney bean germplasm line (AO-1012-29-3-3A) that has multiple virus and bean weevil (storage pest) resistances. This bean germplasm line has I and bc-12 genes that confer complete resistance to BCMV and BCMNV.…”
Section: Planting Of Resistant Materialsmentioning
confidence: 99%
“…Studies have addressed some of these biotic constraints in Tanzania and solutions found for some (Fivawo and Msolla, 2011;Mourice and Tryphone, 2012;Langwerden, 2014;Kusolwa et al, 2016). There have also been reviews on different aspects of common bean production in the country (Hillocks et al, 2006;Tryphone et al, 2013) but none focused on common bean virus diseases, which can cause 100% yield loss (Worrall et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Arcelins are present in all cultivated Phaseolus species, but significant diversity and higher concentrations were found in uncooked tepary bean (Tinsley et al 1985) that are partially responsible for their resistance to bruchids (Birch et al 1985;Shade et al 1987). This resistance is being transferred into common bean to increase resistance to Acanthoscelides obtectus (Say) and the Mexican bean weevil, Zabrotes subfasciatus (Boh; Gonzalez Velez et al 2012;Kusolwa et al 2016). Arcelins and other bioactive compounds are degraded during the soaking and cooking process (Kabbara et al 1987) and thus do not pose a problem for human consumption.…”
Section: Introductionmentioning
confidence: 97%